End-user preferences to enhance prospects for varietal acceptance and adoption in potato breeding in Uganda - Jantongo, J.S.; Tinyiro, S.E.; Nakitto, M.; Serunkuma, E.; Namugga, P.; Ayetigbo, O.; Mayanja, S.; Moyo, M.; Ssali, R.T.; Mendes, T. (Wiley, 2024)
Background Potato varieties have diverse biophysical characteristics, so it is important for breeders to have the capacity to choose those that meet the preferences of end users, such as mealiness, firmness, potato taste; among others. Combining user preferences with descriptive information on the sensory characteristics of boiled potatoes can contribute to the improvement of consumer-driven varieties. This study aims to factor in the preferences of end users to improve the prospects for varietal acceptance, adoption, and discrimination of genotypes in potato breeding.